Leakage Induced in Eschericia coli Cells by Secondary Metabolites of the J7 Bacterial Isolates from the Rhizosphere of Zingiber officinale Roscoe var. Rubrum - Dianita Febrina Leswara; Nanik Sulistyani; Kintoko Kintoko (Pharmaciana, 2019)
Isolate J7 is a bacterial strain separated from the rhizosphere of Zingiber officinale Roscoe var. Rubrum that potentially produces antibacterial compounds against Escherichia coli. The study aimed to determine the antibacterial activity of the most active fraction of this isolate from its capacity to induce leakage in E. coli cells. The secondary metabolites were extracted from Isolate J7 using ethyl acetate solvent and then fractionated with different ratios of hexane and ethyl acetate solventsâ€•1:0, 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8, 1:9, and 0:1 (v/v), ethyl acetate and methanol with 1:1 (v/v) ratio, and methanol 100%. Fractions were identified based on the spotting on the Thin-Layer Chromatography (TLC) plate. Only the most active fraction was tested to define its ability to cause leakage of cellular components like nucleic acid and protein. The leakage was scanned with a UV-Vis spectrophotometer at wavelengths of 260 and 280 nm. The results showed that F2 was the fraction that prevented the growth of E. coli most actively because it created a zone of inhibition sized 11.58Â±0.95 mm in diameter with the lowest MIC among the other fractions (10%). Also, based on the spectrophotometric analysis, the addition of F2 at concentrations of 10% and 20% resulted in higher levels of protein, DNA, and RNA than the negative control. In conclusion, F2 can cause plasma membrane leakage in E. coli at a concentration of 10%. Another fraction that exhibited antibacterial activity was F3. In the spotting analysis of the TLC plate, F3 appeared to have a spot profile and Rf that were similar to F2 but considerably different from the inactive fractions (i.e., showing no antibacterial activity). Observed with multiple wavelengths, the Rf values of F2 and F3 spots varied between 0.56-0.57 and 0.61-0.62 (254 nm) and 0.47-0.48 and 0.56-0.57 (366 nm), respectively. Because these spot profiles did not appear in the inactive fractions, compounds with this range of Rf values are, thereby, suspected as the active substances that inhibit the growth of E. coli.